The Childfree Phenomenon Through Al Syatibi's Maqasid al Shariah Perspective - Ramzy Zarkasyi; Indah Sari Indah Sari; Khairani Azzahro Khairani Azzahro; Ahmad Fernanda Ahmad Fernanda; Iflahul Hamdi Iflahul Hamdi (Sekolah Tinggi Agama Islam Solok Nan Indah, 2026)
This study examines the childfree phenomenon through the lens of Imam Al-Syatibi's maqasid al-shariah, with particular emphasis on the concept of hifz al-nasl (protection of lineage and future generations). A qualitative research design employing an exploratory document analysis was adopted. The study analyzed classical Islamic legal texts, particularly Al-Muwafaqat fi Usul al-Fiqh, together with peer-reviewed journal articles and other relevant scholarly publications. The collected documents were examined using qualitative content analysis guided by the maqasid al-shariah framework, involving data reduction, thematic categorization, and interpretive analysis. The findings reveal three main points. First, the childfree phenomenon reflects contemporary social transformations shaped by economic considerations, mental health concerns, traumatic experiences, and increasing recognition of reproductive autonomy. Second, Al-Syatibi conceptualizes hifz al-nasl as one of the essential objectives of Islamic law (al-kulliyat al-khams), aimed at preserving both the continuity and the quality of future generations. Third, from a maqasid based perspective, the permanent decision to remain childfree without a necessity (darurah) is generally inconsistent with the objective of hifz al-nasl. Nevertheless, in circumstances involving substantial harm, the decision may be assessed through a contextual balancing of maslahah (public interest) and mafsadah (harm). This study highlights the relevance of a maqasid al-shariah oriented approach in formulating adaptive Islamic legal reasoning that responds to contemporary social realities while preserving the fundamental objectives of Islamic law